Fungal contamination and chemical assessment of Iranian Doogh marketed in Hamadan, Iran - Abbas Ali Sari; Negar Sasanian; Mohammadreza Pajohi-Alamoti; Nazanin Sasanian (Gonabad University of Medical Sciences, 2018)
Doogh is an Iranian traditional dairy-based drink product formally identified as Iranian national drink. This fermented acidified drink has high nutritional value and pleasant organoleptic properties. Samples (n= 120) collected from both industrial and traditional Doogh retail stores in Hamadan in 2015 were analyzed for total solids (%), pH, titratable acidity, salt (%), mold and yeasts count (cfu/ml) according to the Iranian National Standards (no. 2453). Results showed that 100% and 24% of the traditional and industrial Doogh samples had fungal contamination over than 100 cfu/ml, respectively. Moreover, the mean values of titratable acidity, pH, salt, and total solids showed a significant between-group difference. According to this study, employing hygiene programs regarding the production processes is highly recommended.